Analysis Journal of Habits of Mind Through the Realistic Mathematics Education (RME) Approach in Improving Reasoning Ability - Ezra P Simarmata (Jurnal Fibonaci: Jurnal Pendidikan Matematika, 2021)
The purpose of this study was to determine: (1)The tendency of the habits of mind towards reasoning abilities, (2) the effect of Realistic Mathematics Education (RME) in improving reasoning abilities, and (3) the advantages and disadvantages of Realistic Mathematics Education (RME). This study uses a qualitative descriptive research with a literature study method in the Digital Library of the State University of Medan. The data analysis technique used is the data analysis technique of Miles and Huberman, which consists of the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the analysis obtained are: (1) Habits of mind affect reasoning ability with an average effect size value of 1.131687 in the high category. (2) Realistic Mathematics Education (RME) has an effect on reasoning ability with an average effect size value of 1,572938 in the very high category. (3) The advantages of the RME approach are that students are more active in building their own knowledge, the learning process becomes more interesting because it uses real experiences / problems in everyday life that occur around them, and students are given the opportunity to think, argue mathematically on solving problems. which are given. Meanwhile, the advantages of the RME approach are that in the learning process the smarter group dominates than the less intelligent group, the low level of teacher ability results in misconceptions about the material, the use of time in the RME approach process is quite long and the search for questions related to the RME approach. the hard one